Cryo‐EM structure of the CENP‐A nucleosome in complex with phosphorylated CENP‐C. (19th January 2021) - Ariyoshi, Mariko; Makino, Fumiaki; Watanabe, Reito; Nakagawa, Reiko; Kato, Takayuki; Namba, Keiichi; Arimura, Yasuhiro; Fujita, Risa; Kurumizaka, Hitoshi; Okumura, Ei‐ichi; Hara, Masatoshi; Fukagawa, Tatsuo
Abstract: The CENP‐A nucleosome is a key structure for kinetochore assembly. Once the CENP‐A nucleosome is established in the centromere, additional proteins recognize the CENP‐A nucleosome to form a kinetochore. CENP‐C and CENP‐N are CENP‐A binding proteins. We previously demonstrated that vertebrate CENP‐C binding to the CENP‐A nucleosome is regulated by CDK1‐mediated CENP‐C phosphorylation. However, it is still unknown how the phosphorylation of CENP‐C regulates its binding to CENP‐A. It is also not completely understood how and whether CENP‐C and CENP‐N act together on the CENP‐A nucleosome. Here, using cryo‐electron microscopy (cryo‐EM) in combination with biochemical approaches, we reveal a stable CENP‐A nucleosome‐binding mode of CENP‐C through unique regions. The chicken CENP‐C structure bound to the CENP‐A nucleosome is stabilized by an intramolecular link through the phosphorylated CENP‐C residue. The stable CENP‐A‐CENP‐C complex excludes CENP‐N from the CENP‐A nucleosome. These findings provide mechanistic insights into the dynamic kinetochore assembly regulated by CDK1‐mediated CENP‐C phosphorylation. Synopsis: Phosphorylation of kinetochore protein CENP‐C regulates its binding to the CENP‐A nucleosome. Cryo‐EM reveals how CENP‐C phosphorylation regulates CENP‐A binding and provides insights into a dynamic kinetochore assembly mechanism during mitosis. The C‐terminal region of CENP‐C adopts a stable fold upon CENP‐A nucleosome binding. CDK1 phosphorylation of CENP‐C stabilizes the complex structure with the CENP‐A nucleosome via an intramolecular interaction. CENP‐C binds the RG loop of the CENP‐A nucleosome, which is recognized by another CENP‐A‐binding protein, CENP‐N. The stable CENP‐A‐ CENP‐C complex excludes CENP‐N from the CENP‐A nucleosome. Abstract : Observation of how an extended CENP‐C peptide binds centromeric nucleosomes explains regulation of kinetochore assembly by CDK1 phosphorylation and the mutual exclusion of CENP‐C/CENP‐N recognition.